PENGARUH PENGEMBANGAN KARIR DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL ALPHA PEKANBARU - Andri Jeco Forito; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study used 47 respondents consisting of all employees of Alpha Hotel Pekanbaru. The purpose of this study was to determine and analyze the effect of career development and job satisfaction on employee performance at Alpha Hotel Pekanbaru simultaneously and partially. The method used in this research is a quantitative descriptive method with the SPSS program. This study uses several analytical tests, namely, validity test, reliability test, multiple linear analysis test, coefficient of determination test (R²), hypothesis testing with t test (partial), and F test (simultaneous). The results showed that testing the hypothesis of career development has a significant effect on the performance of employees at Alpha Hotel Pekanbaru, and job satisfaction has a significant effect on the performance of Alpha Hotel Pekanbaru employees. It can be concluded that career development and job satisfaction have a significant effect on the performance of Alpha Hotel Pekanbaru employees. Keywords: Career Development, Job Satisfaction, Employee Performance